Cold rolled tungsten (W) plates and foils: Evolution of the microstructure. (November 2016) - Bonk, Simon; Reiser, Jens; Hoffmann, Jan; Hoffmann, Andreas
Abstract: This paper is the first part of our series on ultrafine-grained (UFG) tungsten produced by cold rolling. The aim of our project is to investigate the correlation between microstructure, mechanical properties and deformation mechanisms in UFG tungsten, a material interesting for future high-temperature applications. For this purpose, a batch of tungsten sheets with different thicknesses has been produced by subsequent cold rolling out of a single sintered compact. The aim of this paper is to characterise the microstructure of the as-received tungsten sheets. Quantitative grain size analysis by EBSD confirms a grain refinement by cold rolling well down into the UFG-regime, reaching 240 nm in the S-direction for the 100 μm foil. The grain refinement comes with an increase in the number of HAGBs, while LAGBs show no correlation with the degree of deformation introduced by cold rolling. All plates are distinctively textured, the main texture being the {001}〈110〉-orientation (rotated cube texture). Vickers microhardness measurements confirm a steady increase in hardness with advanced rolling up to 687 kg/mm 2 for the 100 μm foil. This indicates that the one-dimensional grain refinement to UFG by cold rolling is sufficient to achieve properties comparable to other UFG tungsten specimens. Therefore, it can be concluded that the batch of samples introduced in this paper will be fit to investigate the evolution of mechanical properties and deformation mechanisms in correlation with the microstructure. Graphical abstract: Highlights: A batch of tungsten (W) sheets with thicknesses between 1 mmand 0.1 mm has been rolled out of a single sintered compact. The cold rolling induced evolution of the microstructure has been assessed. Cold rolling leads to a steady decrease of grain size well down into the UFG-regime, reaching 240 nm for the 100 μm foil. Cold rolling induces a rotated cube texture and increases the fraction of HAGBs. The hardness evolution by cold rolling follows Hall-Petch relation: HV ( d ) = 118 ∙  d − 1/2  + 448